Does One Plus One Always Equal Two? Examining Complementarities in Educational Interventions - Umut Özek (Center for Economic Studies and ifo Institute (CESifo), 2024)
Public policies targeting individuals based on need often impose disproportionate burden on communities that lack the resources to implement these policies effectively. In an elementary school setting, I examine whether community-level interventions focusing on similar needs and providing resources to build capacity in these communities could improve outcomes by improving the effectiveness of individual-level interventions. I find that the extended school day policy that targets lowest-performing schools in reading in Florida significantly improved the effectiveness of the third-grade retention policy in these schools. These complementarities were large enough to close the gap in retention effects between targeted and higher-performing schools.
Keywords: I20; I28; 330; educational interventions; complementarities; disadvanted communities